Polarity in sociology of knowledge: the relationship between disciplinarity, curriculum, and social justice. Issue 2 (3rd April 2019) - Shalem, Yael; Allais, Stephanie
Abstract: This paper examines two influential views within the sociology of knowledge, specifically in literature examining relationships between knowledge, curriculum, and social justice, located in the South African context of extreme inequality and poverty. The first emphasizes the role of disciplines in creating criteria of powerful knowledge, arguing that knowledge must be evidence‐based, generalizable, and revisable. The second argues for the importance of the social origins of knowledge for reasons both of strengthening knowledge and creating curricula that foster confidence in young scholars. We then draw on what we see as the strongest claims of each view and explore the value they bring to thinking about knowledge and curriculum debates raised by community of practitioners within three disciplines in the social science – economics, education studies, and history. Our brief consideration of these disciplines reveals that different disciplines face specific challenges which transverse, in different ways, the polarity which characterizes the debate so far. Strong aspects of each view feature in the development of each of the three disciplines, some in negative ways. This is an interesting finding, which demonstrates that principled debates couched in epistemological terms, when applied to specific disciplines, do not remain as a simple binary.